Amateur boxer biomechanics and punch force - Mack, J.; Stojsih, S.; Sherman, D.; Dau, N.; Bir, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The current study investigates the correlation between punch biomechanics and punch force in amateur male boxers (n=39). A Hybrid III 50th percentile male dummy was used to gather punch force values. TrackEye Motion Analysis (TEMA) was used to measure the velocity of each boxer's punch. Lower body force values were determined using the Functional Assessment of Biomechanics (FAB) system. Two types of punches, hooks and straights, were analyzed. It was determined that punch forces correlated more strongly to hand velocity than to lower body forces. Punch force correlated to hand velocity with R2 values of 0.380 and 0.391 for hook and straight punches, respectively (p<0.001). Punch force correlated to lower body forces with R2 values of 0.103 and 0.099, respectively (p<0.05).